Abdominal mass in a septic infant: Case of a fatal intraluminal intestinal hematoma - Mana Taweevisit; Paul Scott Thorner (Elsevier, 2021)
An 11-month-old boy was admitted to the intensive care unit with pneumonia and severe respiratory distress syndrome, associated with septic shock and disseminated intravascular coagulation (DIC). Ten days after admission, a 10-cm abdominal mass was detected in the right lower quadrant. Ultrasound showed a markedly thickened and edematous bowel wall interpreted as severe acute enterocolitis. The patient died two days later. At autopsy, there was generalized bowel distension with an intraluminal hematoma extending from the jejunum to the ascending colon. Non-traumatic, spontaneous intraluminal hematoma is a rare cause of an abdominal mass. Patients with DIC are at risk for this event and the smaller bowel lumen in children makes them especially at risk for obstruction. Prompt recognition of this condition is crucial for a successful patient outcome.